Rapid titrimetric and spectrophotometric determination of ofloxacin in pharmaceuticals using N-bromosuccinimide - Kanakapura Basavaiah Vinay; Hosakere Doddarevanna Revanasiddappa; Okram Zenita Devi; Pavagada Jagannathamurthy Ramesh; Kanakapura Basavaiah (Brazilian Journal of Pharmaceutical Sciences, 2011)
One titrimetric and two spectrophotometric methods have been described for the determination of ofloxacin (OFX) in bulk drug and in tablets, employing N-Bromosuccinimide as an analytical reagent. The proposed methods involve the addition of a known excess of NBS to OFX in acid medium, followed by determination of unreacted NBS. In titrimetry, the unreacted NBS is determined iodometrically, and in spectrophotometry, unreacted NBS is determined by reacting with a fixed amount of either indigo carmine (Method A) or metanil yellow (Method B). In all the methods, the amount of NBS reacted corresponds to the amount of OFX. Titrimetry allows the determination of 1-8 mg of OFX and the calculations are based on a 1:5 (OFX:NBS) reaction stoichiometry. In spectrophotometry, Beer's law is obeyed in the concentration ranges 0.5-5.0 µg/mL for method A and 0.3-3.0 µg/mL for method B. The molar absorptivities are calculated to be 5.53x10(4) and 9.24x10(4) L/mol/cm for method A and method B, respectively. The methods developed were applied to the assay of OFX in tablets, and results compared statistically with those of a reference method. The accuracy and reliability of the methods were further ascertained by performing recovery tests via the standard-addition method. Descrevem-se métodos, um titulométrico e dois espectrofotométricos, para a determinação de ofloxacino (OFX) na matéria-prima e em comprimidos, empregando a N-bromossuccinimida (NBS) como reagente analítico. Os métodos propostos envolvem a adição de excesso conhecido de NBS ao OFX, em meio ácido, seguida de determinação do NBS que não reagiu. Na titulometria, o NBS que não reagiu é determinado iodometricamente e na espectrofotometria, o NBS que não reagiu é determinado pela reação com quantidade fixa de índigo carmim (Método A) ou amarelo de metanila (Método B). Em todos os métodos, a quantidade de NBS que reagiu corresponde à quantidade de OFX. A titulometria permite a determinação de 1-8 mg de OFX e os cálculos se baseiam na estequiometria de reação de 1:5 (OFX:NBS). Na espectrofotometria, a Lei de Beer é obedecida nas faixas de concentração de 0,5-5,0 µg/mL, para o método A, e de 0,3-3,0 µg/mL, para o método B, respectivamente. Os métodos desenvolvidos foram aplicados para o teste de OFX em comprimidos e os resultados foram comparados estatisticamente com aqueles do método de referência. A precisão e a confiabilidade dos métodos foram, posteriormente, verificadas por meio dos testes de recuperação via método de adição de padrão.